Dichloridobis(1,3-diisopropyl-4,5-dimethyl-1H-imidazol-3-ium-2-thiolate-κS)copper(II) - Flörke, Ulrich (International Union of Crystallography, 2013)
The molecular structure of the title compound, [CuCl(2)(C(11)H(20)N(2)S)(2)], shows the Cu(II) atom with a distorted tetrahedral geometry from two Cl atoms [Cu—Cl = 2.2182 (6) Å] and two thione S atoms [Cu—S = 2.3199 (6) Å]. The angles at the copper cation, which lies on a twofold rotation axis, are Cl—Cu—Cl = 142.84 (4)°, Cl—Cu—S = 94.80 (2) and 99.97 (2)°, and S—Cu—S = 132.46 (4)°. The planes of the two imidazolium rings make a dihedral angle of 76.92 (8)°.